(untitled) (Fiep Bulletin - online, 2015)
The objective of the study is to investigate and analyze the speech of Physical Education school professors on the distribution of pupils by sex in the classes of the Edmundo Bittencourt State School city of Teresópolis State of Rio de Janeiro. It is a case study, of ethnographic type, where the group of informers was constituted by three male professors and three elementary and middle female teachers. It was originated from the lack of consensus evidenced by us in the pedagogical practice of the Physical Education professors about the choice of a methodology of distribution of the pupils by sex in these classes. For collecting data, we used interviews in focal groups, a free words-association test and non-systematic participant observation. The professors represent the distribution of the pupils by sex as socializing, of little physical confrontation, with differences in relation to the strength and motor ability, sportivized, promoting of the physical training and homogenous as for the strength and motor ability. We concluded that: I in the free recreations the pupils tend to separate by sex; II there is incoherence in relation to the discourse and the practice in most of the professors on the distribution of the pupils by sex; and III the majority of the professors showed a conservative attitude on the pedagogical practice, tending to reproduce as “natural” the gender differences built in the context of the Physical Education school classes.